The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1997
DOI: 10.1523/jneurosci.17-14-05366.1997
|View full text |Cite
|
Sign up to set email alerts
|

A Long-Lasting Calcium-Activated Nonselective Cationic Current Is Generated by Synaptic Stimulation or Exogenous Activation of Group I Metabotropic Glutamate Receptors in CA1 Pyramidal Neurons

Abstract: We have shown previously that a selective metabotropic glutamate receptor (mGluR) agonist, 1S,3R-1-aminocyclopentane-1,3-dicarboxylate (1S,3R-ACPD), evokes an inward current in CA1 pyramidal neurons of rat hippocampal slices in the presence of K ϩ channel blockers (Cré pel et al., 1994). This current has been characterized as a Ca 2ϩ -activated nonselective cationic (CAN) current. Using whole-cell patch-clamp recordings and intracellular dialysis, we now have identified the mGluR subtype and the mechanisms und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
156
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 160 publications
(170 citation statements)
references
References 71 publications
(91 reference statements)
14
156
0
Order By: Relevance
“…Such global elevations in Ca 2+ may also act to enhance membrane depolarization by stimulating an inward Ca 2+ current (I CAN ). 2,8 Norepinephrine and dopamine also contribute to the tonic excitatory drive by acting through the cyclic AMP signaling pathway to enhancing the activity of the hyperpolarizingactivated cyclic nucleotide-gated (HCN) channel responsible for the I h current (Fig. 1).…”
Section: Tonic Excitatory Drivementioning
confidence: 99%
“…Such global elevations in Ca 2+ may also act to enhance membrane depolarization by stimulating an inward Ca 2+ current (I CAN ). 2,8 Norepinephrine and dopamine also contribute to the tonic excitatory drive by acting through the cyclic AMP signaling pathway to enhancing the activity of the hyperpolarizingactivated cyclic nucleotide-gated (HCN) channel responsible for the I h current (Fig. 1).…”
Section: Tonic Excitatory Drivementioning
confidence: 99%
“…Other mechanisms mediating mGluR-induced cationic currents include Ca 2ϩ -dependent or -independent selective cation currents (Congar et al 1997;Crepel et al 1994;Guerineau et al 1995;Zheng et al 1995), voltage-dependent Ca 2ϩ channels, and Ca 2ϩ -sensitive transient receptor potential (TRP)-like currents (Gee et al 2003). Other studies have linked Group I mGluR activation to inhibition of K ϩ currents, including the delayed outward rectifier (I K ) (Charpak et al 1990;Hay and Lindsley 1995;Lüthi et al 1996;Schrader and Tasker 1997), resting K ϩ current (Guerineau et al1994;Schrader and Tasker 1997), and slow Ca 2ϩ -dependent K ϩ current (I AHP ) (Abdul-Ghani et al 1996a,b; Gerber et al 1992; Schrader and Tasker 1997).…”
Section: Contribution Of the Na ϩ -Ca 2ϩ Exchange Currentmentioning
confidence: 99%
“…Furthermore, we examined whether channel modulations driven by other PLC-coupled receptors are also Ca 2+ dependent. We found that the activation of I-mGluRs, like muscarinic activation, induced the activation of NSC-like channels and inhibition of K + channels, and that these Many studies have shown the Ca 2+ -dependent property of NSC channel activation (Blair et al, 2009;Congar et al, 1997;Fraser and MacVicar, 1996;Gee et al, 2003;Magistretti et al, 2004;Yan et al, 2009;Zhang et al, 2011), and it has been mostly interpreted as the Ca 2+ dependence of NSC channel itself. Our data do not negate the Ca 2+ dependence of NSC channel itself, but suggest that caution must be exercised in interpreting experimental data (Blair et al, 2009).…”
Section: Discussionmentioning
confidence: 86%
“…Activation of G q/11 -coupled receptors induces activation of non-selective cation (NSC) channels and inhibition of K + channels (Delmas et al, 2004;Delmas and Brown, 2005;Moran et al, 2004), both of which contribute to depolarization, in various types of neurons including hippocampal neurons (Chiang et al, 2010;Congar et al, 1997;Gee et al, 2003). In the present study, we used these channel modulations as examples of cellular responses elicited by receptor-driven PLCβ activation, and examined whether they are Ca 2+ dependent.…”
Section: Introductionmentioning
confidence: 99%